Factors Influencing the Adoption of Wondr by BNI Among Generations Y and Z: A Case Study in Surabaya - Puspa Maya Sari; Rachmad Ari Fattah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the factors influencing the adoption of the Wondr by BNI app among Generation Y and Generation Z in the city of Surabaya. This study employs a quantitative approach with an explanatory design. Data were collected via a questionnaire distributed to respondents in the Generation Y and Generation Z categories, using purposive sampling. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that ease of use, utility, trust, financial benefits, and social influence significantly affect app adoption. Among these variables, the factors of usefulness and ease of use are the most dominant determinants, indicating that younger generations tend to prioritize functionality in technology use. Additionally, differences in characteristics were found between Generation Y and Generation Z, where Generation Z is more influenced by ease of use and social factors, while Generation Y places greater emphasis on usefulness and trust. This study provides a theoretical contribution to the development of technology adoption research in the context of banking super apps, as well as practical implications for the development of more effective digital banking service strategies.